2019
DOI: 10.1097/md.0000000000017358
|View full text |Cite
|
Sign up to set email alerts
|

Continuous femoral nerve block is more effective than continuous adductor canal block for treating pain after total knee arthroplasty

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 21 publications
0
47
0
Order By: Relevance
“…[ 5 , 6 ] Several pain relief methods are available for postoperative analgesia, including patient-controlled intravenous analgesia, intravenous opioids, femoral nerve block, local infiltration analgesia, and epidural. [ 7 10 ] However, the most suitable analgesic method remains controversial. Recently, published studies have reported that the adductor canal block (ACB) provides effective postoperative analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 , 6 ] Several pain relief methods are available for postoperative analgesia, including patient-controlled intravenous analgesia, intravenous opioids, femoral nerve block, local infiltration analgesia, and epidural. [ 7 10 ] However, the most suitable analgesic method remains controversial. Recently, published studies have reported that the adductor canal block (ACB) provides effective postoperative analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] Some of the high quality studies have confirmed that ACB and FNB, in total knee arthroplasty, can achieve similar postoperative analgesic effect, but patients with ACB can obtain better early rehabilitation compared with those with FNB. [ 5 9 ] Similarly, in a prospective randomized, controlled trial, patients who underwent ACLR were randomized to receive either FNB or ACB, ACB exhibited early relative sparing of quadriceps strength at 6 to 8 hours postanesthesia compared with FNB. [ 1 , 11 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, FNB is followed by a significant decrease in quadriceps muscle strength, resulting in delayed mobilization, which is associated with the potential risk of falling. [ 5 , 6 ] Within this context, a growing body of evidence supports the use of an adductor canal block (ACB), which offers pure sensory block with minimal motor involvement in patients undergoing ACLR. [ 7 ] An ACB can be expected to include the saphenous nerve, vastus medialis, medial femoral cutaneous, articular branches from the obturator, and the medial retinacular nerves.…”
Section: Introductionmentioning
confidence: 99%
“…This distribution supplies the medial, anterior, and lateral aspects of the knee. In recent years, the ACB has been proposed as a potential successor to the FNB [43][44][45][46] .…”
Section: Therapeutic Consideration Of Urvi Marmamentioning
confidence: 99%